Sexual behaviors and associated factors among antiretroviral treatment attendees in Ethiopia - Demissie K (Dove Medical Press, 2015)
Kassahun Demissie,1 Shifera Asfaw,2 Lakew Abebe,2 Getachew Kiros2 1Addis Ababa Regional Laboratory, Ethiopia; 2Department of Health Education and Behavioral Science, College of Public Health and Medical Sciences, Jimma University, Ethiopia Background: Human immunodeficiency virus (HIV)/acquired immune deficiency syndrome is one of the major public health problems throughout the world. Nowadays, antiretroviral treatment (ART) is available in health institutions and HIV-positive individuals who are eligible for ART are taking it. But studies show reinfection of HIV is occurring in them for unknown reasons. Purpose: This study aimed to assess risky sexual practice and associated factors among HIV-positive ART attendees. Methods: An institution-based cross-sectional study was employed in ten randomly selected health centers in Addis Ababa, between October 05 and November 05, 2013. Simple random sampling technique was employed to select 376 respondents for face-to-face interviews from ART registration book. After the data collection process, data were entered and analyzed using the SPSS version 20 statistical package. Then the effect of each variable was observed by regression analysis to identify the predictors for risky sexual practice at a significant level of P<0.05. Results: A total of 376 respondents were included in the study, with 100% response rate. The mean age of the total respondents was 35.28±8.94 (standard deviation). Of the 376 respondents, 30.4% had a history of risky sexual practice, which was inconsistent condom use in the last 3 months prior to the study period. Factors associated with risky sexual practice included alcohol consumption (adjusted odds ratio [AOR] =2.01, 95% CI: 1.07, 3.77), being single (AOR =0.29, 95% CI: 0.15, 0.59) and widowed (AOR =0.32, 95% CI: 0.13, 0.77) respondents, and the gender of the respondents, with an AOR of 1.55 (95% CI: 1.01, 2.33), shows a significant relationship with risky sexual behavior. Conclusion: Generally, a significant number (30%) of the respondents engaged in risky sexual behavior; so health providers should encourage, support, and allow clients to effectively use condoms during their sexual practice. Keywords: sexual behaviors, inconsistent condom use, ART user, HIV prevention, reinfection, alcohol consumption